2018
DOI: 10.22489/cinc.2018.254
|View full text |Cite
|
Sign up to set email alerts
|

Robust Assessment of Photoplethysmogram Signal Quality in the Presence of Atrial Fibrillation

Abstract: A great deal of algorithms currently available to assess the quality of photoplethysmogram (PPG) signals is based on the similarity between pulses to derive signal quality indices. This approach has limitations when pulse morphology become variable due to the presence of some arrhythmia as in the case of atrial fibrillation (AFib). AFib is a heart arrhythmia characterized in the electrocardiogram mainly by an irregular irregularity. This arrhythmicity is reflected on PPG pulses by the presence of non-uniform p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Manual annotation [51][52][53][54] Guided By rules [55,56] By reference signal [35,[57][58][59] Perturbations artificially created during recording PR = Pulse Rate, HR = Heart Rate, ECG = Electrocardiogram, cPPG = Contact Photoplethysmography.…”
Section: References Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manual annotation [51][52][53][54] Guided By rules [55,56] By reference signal [35,[57][58][59] Perturbations artificially created during recording PR = Pulse Rate, HR = Heart Rate, ECG = Electrocardiogram, cPPG = Contact Photoplethysmography.…”
Section: References Detailsmentioning
confidence: 99%
“…They also compared their method using SVM with two other algorithms [43,77] on the Capnobase dataset [83]. Pereira et al [52] also found the best performance with their SVM classifier against seven representative methods [42,43,68,70,77,89,90]. Elgendi used the SVM algorithm to find the most discriminant feature to classify the quality of a PPG pulse [51].…”
Section: Machine Learningmentioning
confidence: 99%
“…A body of studies has proposed approaches for pulsatile signal quality assessment that are applicable to PPG signals. Early approaches were based on measures of similarity between consecutive pulses (Karlen et al 2012, Pereira et al 2018, nevertheless, they fail to correctly assess the signals quality in the case of AF because consecutive PPG pulses become morphology different (Asgari et al 2010). Machine learning (ML) techniques can overcome this problem since they are trained with AF cases (Pereira et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Early approaches were based on measures of similarity between consecutive pulses (Karlen et al 2012, Pereira et al 2018, nevertheless, they fail to correctly assess the signals quality in the case of AF because consecutive PPG pulses become morphology different (Asgari et al 2010). Machine learning (ML) techniques can overcome this problem since they are trained with AF cases (Pereira et al 2018). In our previous work, we proposed a two-class SVM-based quality assessment model with a 0.95 accuracy that showed to be more accurate than the approaches reported in the literature that were based on either traditional statistical (Asgari et al 2010, Sukor et al 2011, Li and Clifford 2012, Karlen et al 2012, Orphanidou et al 2015, Liu et al 2016 or other ML methods (Chong et al 2014).…”
Section: Introductionmentioning
confidence: 99%